The Role of Nursing in Managing Chronic Illness: A Review of Patient Outcomes and Quality of Life - Alruwaili , Majdah Jalal Juhayyim; Alwallah , Suyuf Ahmed; ALRuwaili, Faizah Shuwayhit; asmari , Mashael Ali; AlRowily, Reem Thamer Salam; Alghamedi , Fatimah Hussien; Alenazi , Eman Mudhhi; Alanazi , Amlak Dhumayri; Alshammari, Wansah Fahad; Alghamedi , Nawal Hussein Abdullah (Journal of Ecohumanism, 2024)
The management of chronic illness is a growing priority in healthcare, with nursing playing a critical role in improving patient outcomes and quality of life. This review explores the various nursing interventions that support chronic illness management, including patient education, symptom monitoring, and emotional support. By providing personalized care and fostering self-management skills, nurses contribute to reduced hospital readmissions, improved medication adherence, and enhanced physical and mental health outcomes. Additionally, nursing care significantly influences patients’ quality of life, offering emotional support that positively impacts their mental well-being and overall satisfaction. Despite the benefits, challenges such as limited resources, time constraints, and nursing burnout remain barriers to effective care. This review emphasizes the need for continued support for nursing roles in chronic illness management, policy adjustments to address resource limitations, and integration of technology to enhance care delivery. Overall, a strengthened nursing role in chronic illness management not only benefits patient outcomes but also enhances patients’ quality of life, underscoring the importance of investment in nursing care to meet the demands of chronic illness in healthcare.